Gas separation membrane

CN117545544BActive Publication Date: 2026-10-27SUPERSTAR HIGH PERFORMANCE MATERIALS (SUZHOU) CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202280044834.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-06-29
Filing Date
2022-06-14
Publication Date
2026-10-27
Estimated Expiration
2042-06-14

Smart Images

  • Figure CN117545544B_ABST
    Figure CN117545544B_ABST
Patent Text Reader

Abstract

A gas separation membrane comprising layers of: (i) a support layer; (ii) a buffer layer; (iii) a discriminating layer; (iv) an optional fluorinated polymer layer; and (v) an optional protective layer; wherein: (a) the buffer layer (ii) and the discriminating layer (iii) each independently comprise groups of Formula (1): M-(O-) x Formula (1) wherein: each M is independently a metal or metalloid atom; O is an oxygen atom; and each x independently has a value of at least 4; (b) the buffer layer (ii) comprises a surface comprising 4 to 10 atomic % of M of groups of Formula (1), wherein M is as defined above; (c) the discriminating layer (iii) comprises a surface comprising greater than 10 atomic % of M of groups of Formula (1), wherein M is as defined above; and (d) layer (ii) is between layers (i) and (iii).
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to gas separation membranes (GSM), their preparation, and their uses.

[0002] US10,427,111 describes a GSM with high selectivity under high feed pressure. The GSM comprises a siloxane layer having a specified O / Si ratio at a certain depth. However, US10,427,111 does not mention the ability of said film to resist deformation under pressure.

[0003] One of the problems with currently available gas separation filters (GSMs) and modules containing them is that their selectivity decreases significantly over time when used to separate polar and nonpolar gases. This problem is particularly severe when gas mixtures containing polar and nonpolar gases contact the GSM at high feed pressures and temperatures. In these cases, the GSM typically deforms due to normal (often referred to as "imprinting") and / or tangential / shear stresses. This problem is especially pronounced when the GSM contacts macroporous diaphragms or carrier elements, which can often "imprint" their patterns onto the GSM, resulting in deformation or scratching due to tangential / longitudinal / shear displacement / elongation. This can thus reduce the selectivity and / or gas separation efficiency of the GSM. There is a need for GSMs and modules containing them that maintain their selectivity or only allow it to decrease slowly when exposed to feed gas mixtures at high pressures and / or temperatures.

[0004] According to a first aspect of the present invention, a gas separation membrane is provided, comprising the following layers:

[0005] (i) Support layer;

[0006] (ii) Buffer layer;

[0007] (iii) Discrimination layer;

[0008] (iv) An optional fluoropolymer layer; and

[0009] (v) Optional protective layer;

[0010] in,

[0011] (a) The buffer layer (ii) and the discrimination layer (iii) each independently contain groups of formula (1):

[0012] M-(O-) x

[0013] Equation (1)

[0014] in:

[0015] Each M is an independent metal or metalloid atom;

[0016] O represents an oxygen atom; and

[0017] Each x value is independently at least 4;

[0018] (b) The buffer layer (ii) comprises a surface of M containing 4 to 10 atomic percent of a group of formula (1), wherein M is as defined above;

[0019] (c) The distinguishing layer (iii) comprises a surface of M containing more than 10 atomic percent of a group of formula (1), wherein M is as defined above; and

[0020] (d) Layer (ii) is located between layers (i) and (iii).

[0021] In this specification, the term "comprising" should be interpreted as requiring the presence of the stated part, step, or component, but does not exclude the presence of one or more additional parts, steps, or components. Referring to an element with the indefinite articles "a(a)" or "an(an)" does not preclude the possibility of the existence of more than one element, unless the context explicitly requires one and only one element. Therefore, the indefinite articles "a(a)" or "an(an)" generally mean "at least one". The buffer layer (ii) is generally abbreviated as "BL", and the discrimination layer (iii) is generally abbreviated as "DL".

[0022] In this specification, the term "separation or discrimination layer" refers to a layer with separation selectivity. A layer with separation selectivity means that, when forming a membrane with a thickness of 0.05 to 30 μm and supplying pure gases of carbon dioxide (CO2) and methane (CH4) to the resulting membrane at a temperature of 40°C by setting the total pressure on the gas supply side to 0.5 MPa, the carbon dioxide permeability coefficient (P0) of the layer is [not specified]. CO2 ) and the permeability coefficient of methane (P) CH4 The ratio of (P) CO2 / P CH4 The value is 10 or higher. Attached Figure Description

[0023] In the attached diagram:

[0024] Figure 1 This is a schematic vertical cross-sectional view showing a portion of a conventional gas separation element, including an external gas separation membrane and an internally shaped macroporous sheet.

[0025] Figure 2 It is first in Figure 1 The diagram shows a schematic vertical cross-sectional view of a conventional gas separation element in use, and illustrates the vertical deformation of the membrane wall under high gas pressure.

[0026] Figure 3 It is first in Figure 1The diagram shows a schematic vertical cross-sectional view of a conventional gas separation element in use, and illustrates the vertical (or "normal") and longitudinal deformation of the membrane wall. Longitudinal deformation is caused by longitudinal tension, shear stress, and scratching of the membrane.

[0027] Figure 4 This is a diagram showing the atomic percentage of various components in a membrane comprising a discrimination layer (“DL”), a buffer layer (“BL”), and a trench layer (“GL”), which is part of the support layer of the gas separation membrane described in Example 1.

[0028] exist Figure 1 The image shows a portion of a conventional gas separation element used in a conventional gas separation module. Figure 1 In this conventional gas separation element (10), there are a first gas separation membrane (7), a second gas separation membrane (8), and a macroporous sheet (19) disposed between these gas separation membranes. The macroporous sheet (19) has protrusions (12) and recesses (grooves) (13) alternately formed at constant intervals on its upper surface. The grooves form the main channels for the flow of permeating gas.

[0029] Figure 2 It is shown in Figure 1 A schematic vertical cross-sectional view of the vertical (or "normal") deformation (imprint) of the gas separation membrane (7) under high pressure in a conventional gas separation element (10). Figure 2 In this process, the feed gas flows above the first gas separation membrane (7) and below the second gas separation membrane (8), and partially permeates the gas separation membranes (7) and (8) to reach the macroporous sheet (19). In this case, if the feed gas is supplied under high pressure, the first gas separation membrane (7) located on the rough side of the macroporous sheet (19) is partially pressed into the groove (13) and deformed / imprinted. The pressure acting on the first gas separation membrane (7) is indicated by arrow (14), and the pressure acting on the second gas separation membrane (8) is indicated by arrow (15). The deformation of the first gas separation membrane (7) partially closes the groove (13), which is the main path of the gas flow that has permeated through the membrane (7). Furthermore, the vertical deformation (imprinting) damages the first gas separation membrane (7), thereby reducing the performance of the gas separation membrane (7), such as reducing the separation selectivity of the membrane, especially the separation of polar and non-polar gases (e.g., the separation of higher alkanes (e.g., C4H) from a mixture containing both gases). 10 (separation from CO2).

[0030] Figure 3 It shows that first in Figure 1The diagram shows a schematic vertical cross-sectional view of a conventional gas separation element (10) in use, and illustrates the vertical (or “normal”) and longitudinal (lateral) deformation of the gas separation membrane (7). The longitudinal deformation is caused by longitudinal tension, shear stress, and scratching of the gas separation membrane (7). During the assembly and operation of the gas separation membrane module, the macroporous sheet (19) may shift (16) relative to the gas separation membranes (7) and (8). In addition to the vertical deformation caused by high gas pressure during use, the displacement of the macroporous sheet (19) due to friction between the gas separation membranes (7) and (8) and the macroporous sheet (19) results in longitudinal deformation of the gas separation membrane (7).

[0031] Figure 4 The results were obtained by analyzing the surface of the gas separation membrane from Example 1 of the present invention using a ULVAC-PHI surface analysis device. The horizontal axis represents the argon cluster ion beam (Ar-GCIB) sputtering time (indicating the depth being analyzed), and the vertical axis represents the atomic percentage of each element detected at that depth. Figure 4 The order from top to bottom on the right side, Figure 4 The five lines in the diagram represent the atomic percentages of carbon, oxygen, all silicon, silicon present in the groups of formula (2), and silicon present in the groups of formula (1), respectively. Figure 4As can be seen on the left side, the atomic percentage of Si-(O-)4 groups (i.e., Si of formula (1)) on the DL surface is greater than 10%. Furthermore, the atomic percentage of Si-(O-)4 groups in the DL decreases with increasing distance from the surface, and this decrease slows significantly after the DL contacts the BL. Typically, a significantly higher atomic percentage of Si-(O-)4 groups (greater than 15%) is observed from the surface down to the initial 15 nm in the DL (etching time 0 to approximately 2 minutes), indicating a large number of embedded Si-(O-)4 groups in the relatively thin portion of the DL, resulting in high selectivity and acceptable high permeability for gas separation of the membrane. Typically, the atomic percentage of M of the groups of formula (1) on the DL surface not in contact with the BL is greater than 10 atomic%, and the atomic percentage of M of the groups of formula (1) on the DL surface in contact with the BL is typically 4 to 10 atomic%. Generally, in the DL, the atomic percentage of M of the groups of formula (1) gradually decreases with decreasing distance from the BL. In contrast, the atomic percentage of Si with Si-(O-)4 groups is substantially constant throughout the depth of the BL, and the value is 4 to 10% (on its surface and in most or all of its depth). By embedding the substantially constant 4 to 10% atomic percentage of Si-(O-)4 groups beneath the DL in the composition of the BL, the BL can be considered not to act as a separation or discrimination layer due to the insufficient presence of Si-(O-)4 groups. However, since the layer has sufficient Si-(O-)4 groups, it can act as a buffer or relaxation layer to improve the scratching and imprinting properties associated with the fragile high Si-(O-)4 portion inside the DL, as can be observed in the prepared BL-free examples.

[0032] Preferably, layer (i) comprises a porous sheet (“PSM”). The PSM provides mechanical strength to the GSM and reduces the likelihood of damage to the GSM when used under high pressure and / or high temperature.

[0033] Preferred porous support sheet materials include, for example, woven and nonwoven fabrics and combinations thereof.

[0034] PSM can be made of, for example, any suitable polymer or natural fiber. Examples of such polymers include polysulfone, polyethersulfone, polyimide, polyetherimide, polyamide, polyamideimide, polyacrylonitrile, polycarbonate, polyester, polyacrylate, cellulose acetate, polyethylene, polypropylene, polyvinylidene fluoride, polytetrafluoroethylene, poly(4-methyl-1-pentene), and especially polyacrylonitrile.

[0035] Many suitable PSMs are commercially available. Alternatively, PSMs can be prepared using techniques known in the art for preparing such materials. In one embodiment, optional PSMs can be prepared by curing the curable components, for example, in a manner similar to that used for preparing films (which have excessively large pores and cannot distinguish between different gases). Optionally, PSMs can be subjected to corona discharge treatment, glow discharge treatment, flame treatment, ultraviolet irradiation treatment, etc., for example, for the purpose of improving their wettability and / or adhesion.

[0036] As a PSM, ultrafiltration membranes can be used, such as polysulfone ultrafiltration membranes, cellulose ultrafiltration membranes, polytetrafluoroethylene ultrafiltration membranes, polyvinylidene fluoride ultrafiltration membranes, and especially polyacrylonitrile ultrafiltration membranes. Asymmetric ultrafiltration membranes can also be used, including ultrafiltration membranes comprising a porous polymer membrane (preferably with a thickness of 10 to 150 μm, more preferably 20 to 100 μm) and an optional woven or nonwoven fabric support.

[0037] PSMs are preferably as thin as possible, as long as they provide the structural strength required for GSMs.

[0038] Preferably, the PSM includes pores with an average diameter of 0.001 to 10 μm, more preferably 0.01 to 1 μm (i.e., before the PSM has been converted into a gas separation membrane). Preferably, the PSM includes pores having an average diameter of 0.001 to 0.1 μm, more preferably 0.005 to 0.05 μm on its surface. The average pore size can be determined, for example, by scanning electron microscopy (“SEM”) or by cutting through the PSM to observe its surface and again measuring the diameter of the pores within the porous support using SEM, and then calculating the average value.

[0039] The porosity of the PSM surface can also be expressed as % porosity, i.e.

[0040]

[0041] The area required for the above calculations can be determined by examining the surface of the PSM using SEM before converting the PSM into a gas separation membrane. Therefore, in a preferred embodiment, the % porosity of the PSM is >1%, more preferably >3%, particularly >10%, and even more particularly >20%.

[0042] Alternatively, the porosity of the PSM can be characterized by measuring the N2 gas flow rate through the PSM. The gas flow rate can be determined using any suitable technique, such as using Pololux gas available from Polometer.com. TM 1000 units. Typically, the Polorlux... TMThe pressure was set to maximum (approximately 34 bar), and the flow rate (L / min) of N2 gas through the test PSM was measured. For 2.69 cm... 2 With an effective sample area (18.5 mm effective diameter), the N2 flow rate through the PSM at a pressure of approximately 34 bar is preferably >1 L / min, more preferably >5 L / min, particularly >10 L / min, and even more particularly >25 L / min. Higher flow rates are preferred because they reduce the likelihood of the gas flux of the resulting membrane being reduced by the PSM. The pore size and porosity mentioned above refer to the pore size and porosity of the PSM before it is converted into the GSM of this invention.

[0043] The porosity of layer (i) as a whole can be expressed as CO2 gas permeability (in meters). 3 (STP) / m 2 (.s.kPa). When the GSM is intended for gas separation, the CO2 gas permeability of layer (i) is preferably 5 to 150 × 10⁻⁶ kPa. -5 m 3 (STP) / m 2 .s.kPa, more preferably 5 to 100×10 -5 m 3 (STP) / m 2 .s.kPa, optimal value 7 to 70×10 -5 m 3 (STP) / m 2 .s.kPa.

[0044] The average thickness of layer (i) (as a whole) is preferably 20 to 500 μm, more preferably 50 to 400 μm, and particularly 100 to 300 μm.

[0045] Preferably, layer (i) further includes a trench layer (“GL”). When layer (i) includes a trench layer, the trench layer is preferably located between the PSM and layer (ii).

[0046] The total atomic percentage of M present on the surfaces of DL and BL can include M from other sources, and not only M from groups of formula (1). For example, the total atomic percentage of M present on the surfaces of DL and BL includes M from other sources, such as groups from one or more of formula (2):

[0047] M-(O-) z

[0048] Equation (2)

[0049] in:

[0050] M is a metal or metalloid atom;

[0051] O is an oxygen atom; and

[0052] The value of z is 1, 2 or 3.

[0053] Typically, the content of the groups in formula (2) is not included in the selectivity and / or permeability changes within the BL or DL.

[0054] Typically, DL and BL each independently contain groups of formula (1) and groups of formula (2). However, preferably, the mass of the groups of formula (1) in DL is greater than the mass of the groups of formula (2) on the surface.

[0055] In a preferred embodiment, the total atomic percentage of the groups of formula (1) of DL is greater than 10% on average, so as to be selective for gas separation.

[0056] In an even more preferred embodiment, the total number of atoms of M in the group of formula (1) of DL is 30 to 11%, and the thickness range is between the surface of DL and a depth of 20 nm (along the BL direction) so as to be selective and have sufficient permeability (permeability) for gas separation.

[0057] When DL or BL contains a group of formula (2), the M in the group of formula (1) is preferably the same metal or metalloid atom as the M in the group of formula (2) in that layer. However, the M in DL may be the same as or different from the M in BL.

[0058] Preferably, each M is independently silicon, titanium, zirconium, or aluminum. Each M is preferably independently silicon, titanium, zirconium, and / or aluminum.

[0059] Preferably, the surface of DL contains M of a group of formula (1) of greater than 10 atomic% and less than 50 atomic% in particular 12 to 30 atomic% and more particularly 13 to 27 atomic% in the group of formula (1) in the form of M as defined above.

[0060] Preferably, the surface of BL contains 4.5 to 9 atomic percent, and more particularly 5 to 8 atomic percent, of M of formula (1), wherein M is as defined above.

[0061] Preferably, the surface of BL contains 9 to 30.5 atomic percent, and more particularly 20 to 30 atomic percent, of M of formula (2), wherein M is as defined above.

[0062] Preferably, the surface of DL contains M of a group of formula (2) greater than 1 atomic% and less than 25 atomic% in particular 2 to 20 atomic%, and more particularly 3 to 15 atomic% in M ​​of a group of formula (2).

[0063] Preferably, the total atomic percentage of M present on the surface of BL (i.e., M from all sources, such as groups from formula (1) + groups from formula (2)) is 13.5 to 35 atoms, particularly 15 to 33 atoms, and even more particularly 16 to 32 atoms.

[0064] Preferably, the total atomic percentage of M present on the surface of DL (i.e., M from all sources, such as groups from formula (1) + groups from formula (2)) is greater than 11 and less than 50 atoms, particularly 12 to 35 atoms, and more particularly 15 to 33 atoms.

[0065] When M is silicon, the surface of DL preferably contains 10 to 30 atomic percent of M of formula (1), wherein M is silicon.

[0066] When M is aluminum, the surface of DL preferably contains 10 to 40 atomic percent of M of formula (1), wherein M is aluminum.

[0067] When M is titanium, the surface of DL preferably contains 10 to 30 atomic percent of M of formula (1), wherein M is titanium.

[0068] When M is zirconium, the surface of DL preferably contains 10 to 30 atomic percent of M of formula (1), wherein M is zirconium.

[0069] Preferably, the composition of the BL is substantially constant throughout its depth. For example, for at least 80% of the depth of the BL, the atomic percentage of M present in the BL varies by less than 25% relative to the average atomic percentage of M in the BL (more preferably less than 10%, particularly less than 5%). For example, if the average atomic percentage of M in the BL is “X%”, then for at least 80% of the depth of the BL, the atomic percentage of M in the BL is preferably 0.75X to 1.25X (more preferably 0.9X to 1.1X, particularly 0.95X to 1.05X).

[0070] In contrast, the composition of the DL typically varies significantly with depth. For example, the atomic percentage of M of the groups of formula (1) present in the DL varies by at least 5% absolute atomic percentage from one surface of the DL to the other (more preferably 6% to 35% from one surface of the DL to the other). For example, if the average atomic percentage of M of the groups of formula (1) on the surface of the DL in contact with the BL is “Y%”, then the average atomic percentage of M of the groups of formula (1) on the surface of the DL not in contact with the BL is “Y+5%” to “Y+35%” (more preferably “Y+7%” to “Y+30%”).

[0071] Since the atomic percentage of M in the group of formula (1) present on the surface of the DL is greater than 10% (even more preferably 11 to 20%), the DL has a structure containing sufficient M-(O-)4 groups, thereby enabling discrimination between gases that need to be separated (e.g., CO2 separation from CH4). Preferably, the selectivity of the discrimination layer (iii) for one gas to be separated relative to another gas to be separated is at least 10. For example, for the separation of CO2 from CH4, the selectivity of the DL of the present invention is preferably greater than 25. In contrast, the selectivity of the BL layer (ii) of the present invention for one gas to be separated relative to another gas to be separated is preferably much less than 10, for example, less than 8.

[0072] The atomic percentage of M at the surfaces of DL and BL (e.g., groups from formula (1) and groups from formula (2), etc.) can be determined using surface analysis equipment, such as X-ray photoelectron spectroscopy (XPS) (e.g., using GC-IB / XPS gas cluster ion beam XPS). Such equipment can also be used to determine the atomic percentage of M at different depths below the surfaces of DL, BL, and any other layer (e.g., GL in its presence). A suitable device for performing surface analysis to determine the atomic percentage of M in each layer is the VersaProbe II XPS device (“ULVAC-PHI”) from Physical Electronics, Inc. The ULVAC-PHI is preferably equipped with monochromatic Al K α (1486.6eV, 15W 25KV) An X-ray source with a grating size of 300 μm × 300 μm was used. To perform charge compensation, low-energy electrons and Ar ions were flooded during the measurement of the atomic percentage of M in each layer. An Ar gas cluster (5 kV, 20 nA, 2 mm × 2 mm) was used for depth profilometry. Based on this analysis, the atomic percentages of M and any other elements (e.g., carbon and oxygen) present in DL and BL could be measured. At the data point with the highest atomic percentage of M, the atomic percentage of M in DL and BL could be determined. This would include M from all sources, such as groups of formula (1) or formula (2) as defined above, and the amount of M in each of these groups could be quantified individually. For example, when M is silicon, the Si-(O)4 group and Si-(O-) z The atomic percentage of silicon in a group (where z is 1, 2, or 3) can be quantified by this method. In the spectrum of Si2p, the binding energy at 102.6 eV is defined for the group of formula (2), while the binding energy at 103.8 eV is defined for the group of formula (1), where formulas (1) and (2) are as defined above. The area ratio of Si2p at 102.6 eV and 103.8 eV can be converted into an atomic ratio (atomic percentage) such that the sum of the areas of the separated peak components will correspond to the atomic percentage of Si.

[0073] In one embodiment, the DL comprises a surface of M containing more than 10 atomic percent of a group of formula (1), and the atomic percent of M of the group of formula (1) present in the DL decreases with increasing distance from the surface in the DL (e.g., along the direction toward BL), optionally decreasing to less than 10 atomic percent of M, where M is as defined above. This can be seen in Figure 4 .

[0074] In contrast to DL, the total atomic percentage of M of the groups of formula (1) present in BL is preferably substantially uniform across most or the entire depth of BL. For example, the variation of the total atomic percentage of M present in BL relative to the average atomic percentage of M in BL throughout the entire depth of BL is less than 25%. In a more preferred embodiment, the variation of M of the groups of formula (1) present in BL is less than 10% (e.g., 8, 7, 6 or 5%) of BL throughout the entire depth (or total thickness) of BL.

[0075] In another aspect of the invention, the oxygen-to-carbon (O / C) ratio of the BL is preferably greater than 0.7 to 1.7 (when the BL is prepared in the absence of oxygen), particularly an O / C ratio of 0.7 to 1.5, which is substantially constant and uniform throughout most of the depth of the BL. For example, when the variation in the ratio over the entire depth or total thickness of the BL is no greater than 10%. In contrast, the DL preferably comprises a surface with an oxygen / carbon (O / C) ratio of 1.8 to 100, more preferably an oxygen / carbon (O / C) ratio of 1.8 to 10 (when the DL is prepared in the presence of oxygen), since the oxygen embedding in the DL decreases in a downward gradient along the direction toward the BL, the value is substantially non-constant, particularly at the surface.

[0076] In another aspect of the invention, the oxygen-silicon (O / total Si) ratio of BL is preferably 1.2 to 1.7, particularly 1.25 to 1.6. In contrast, DL preferably comprises a surface with an O / total Si ratio of 1.8 to 2.5.

[0077] The O / C ratio and O / total Si ratio can be determined using the analytical apparatus described above, for example by X-ray photoelectron spectroscopy (XPS) as described above (e.g., using GC-IB / XPS gas cluster ion beam XPS). The O / C and O / total Si ratios are the ratios of atomic percent as measured by X-ray photoelectron spectroscopy (XPS).

[0078] In one embodiment, layers (ii) and (iii) can be obtained or acquired by a method comprising M in the form of a group of formula (1) and optionally M in the form of a group of formula (2) (as described above). Suitable deposition methods include plasma deposition, particularly plasma deposition of compounds containing M, thereby forming BL and DL comprising groups of formula (1) and optionally groups of formula (2) (as defined above, respectively). Optionally, the plasma deposition process is performed using an atmosphere containing air or oxygen in the presence of a precursor.

[0079] When present, the groups of formula (1) and the groups of formula (2) (as defined and preferred above) are present in layers (ii) and (iii).

[0080] In one embodiment, layer (iii) is applied to layer (ii) using a plasma treatment process employing a precursor compound providing a group of formula (1). For example, as described in US10,427,111, page 40, line 4 to page 41, line 36 (which is incorporated herein by reference), a carrier gas may be used where layer (ii) is preferably oxygen-free (e.g., using an inert gas (e.g., nitrogen) and / or a rare gas (e.g., argon or helium)) and where layer (iii) is preferably oxygen-containing (e.g., O2 alone or a mixture with an inert gas and / or a rare gas (e.g., argon or helium)).

[0081] The plasma treatment process for applying layer (ii) onto layer (i) is preferably performed at a plasma flux of 0.3 to 9.0 J / cm. 2 The energy input level is used (and processed using low-pressure or even (remote) atmospheric plasma). At energy levels below 0.3 J / cm²... 2 In this case, it is impossible to produce a significant layer (ii), and at 9J / cm 2 At higher energy levels, the layer may become dense and brittle, potentially leading to undesirable (unacceptable) scratching and / or imprinting properties.

[0082] The plasma treatment process for applying layer (iii) onto layer (ii) is preferably performed at a plasma flux of 0.3 to 20.0 J / cm. 2 The energy input level is used (and processed using low-pressure or even (remote) atmospheric plasma). At energy levels below 0.3 J / cm²... 2 In this case, a significant discrimination layer (iii) cannot be obtained, only affecting the surface wettability. At 9 J / cm² 2 At higher levels, layer (iii) may become too dense, resulting in very high selectivity but not acceptable permeability.

[0083] The plasma treatment process for applying layer (ii) to layer (i) (or applying layer (iii) to layer (ii)) preferably uses a plasma density of 5 to 500 cm. 3 (STP) / min, more preferably 50 to 200 cm 3 (STP) / min, preferably 80 to 120 cm 3 The process is carried out at an argon flow rate of (STP) / min. In the case of layer (iii), the oxygen (or air) flow rate is preferably 10 cm. 3 (STP) / min, preferably 10 to 100 cm 3 (STP) / min, more preferably 15-100cm 3 (STP) / min, preferably 20 to 50 cm 3 (STP) / min. Low-pressure plasma treatment is preferably carried out at a gas pressure of 0.6 to 100 Pa, more preferably 1 to 60 Pa, and particularly preferably 2 to 40 Pa.

[0084] When a precursor compound containing silica is used in a plasma processing procedure, this results in layer (ii) being deposited on layer (i) (or layer (iii) being deposited on layer (ii)) as a silica-like top surface containing groups of formula (1) and usually also containing groups of formula (2) (both as defined above).

[0085] The average thickness of layer (ii) is typically 1 to 1,500 nm, more preferably 5 to 1,000 nm, and even more preferably 10 to 500 nm.

[0086] In contrast, the average thickness of layer (iii) is typically 1 to 150 nm, more preferably 5 to 120 nm, and even more preferably 10 to 100 nm.

[0087] Typically, the concentration of the groups of formula (1) in layer (iii) gradually decreases as layer (iii) approaches layer (ii). This can be seen in Figure 4 The atomic percentage of Si-(O-)4 groups is much higher than 10 at the surface of layer (ii) furthest from BL (i.e., low etching time), and decreases with increasing depth and proximity to BL (higher etching time). The concentrations of various elements and groups present in the film at different depths can be accurately measured using surface analysis equipment, such as X-ray photoelectron spectroscopy (XPS) as described above. Figure 4 In the study, it was found that the atomic percentage of Si in the Si-(O-)4 group from Example 1 was greater than 10%, and it was also observed that the minimum or stable value was reached at layer (ii)(BL). Furthermore, from... Figure 4As can be seen, the atomic percentage of Si-(O-)4 groups in the buffer layer is relatively constant throughout its entire depth, ranging from 4% to 10%.

[0088] According to a second aspect of the present invention, a method for forming a gas separation membrane according to the first aspect of the present invention is provided, comprising the following steps:

[0089] (a) Layer (ii) is applied to layer (i) by a wet coating process, physical vapor deposition process, chemical vapor deposition process, initiation deposition process, or atomic layer deposition process; and

[0090] (b) Apply layer (iii) (DL) onto layer (ii) (BL) by plasma deposition or plasma processing.

[0091] In a preferred embodiment, layer (ii) is applied to layer (i) via a plasma processing procedure, for example, using a plasma processing apparatus. A preferred plasma processing procedure includes using atmospheric pressure glow discharge plasma. For example, layer (i) may be exposed to atmospheric pressure glow discharge plasma, thereby forming layer (ii) thereon.

[0092] The plasma processing procedure that can be used in step (b) and optionally in step (a) preferably uses a plasma processing apparatus comprising a processing space and a first and a second electrode within that processing space, for generating atmospheric pressure glow discharge plasma between the first and second electrodes. The electrodes can be arranged in various configurations with dielectric barriers. In one configuration, the dielectric barrier of at least one electrode is formed of a polymer film or an inorganic dielectric. Polymers such as polyethylene terephthalate (PET), polytetrafluoroethylene (PTFE), or polyethylene (PE), or ceramics such as silica or alumina, or combinations thereof, can be used. Microporous dielectric materials attached to the electrodes can also be used.

[0093] In a preferred embodiment, layer (iii) is applied onto layer (ii) using atmospheric pressure glow discharge plasma. For example, layer (ii) may be exposed to atmospheric pressure glow discharge plasma to form layer (iii) thereon.

[0094] As described above, the atomic percentage of M of formula (1) in BL(ii) is preferably substantially constant over the entire thickness of BL(layer (ii)), while the atomic percentage of M of the group of formula (1) in DL(layer (iii)) decreases as the distance from the surface of DL to BL(ii) decreases. In contrast to the gradient of the atomic percentage of M of the group of formula (1) along the depth of DL, in order to achieve a substantially constant atomic percentage of M of the group of formula (1) in BL, the manufacturing process of BL is preferably different from that of DL in that a precursor is used in the presence of rare and inert gases and in the absence of oxygen.

[0095] In step (a), the plasma treatment process preferably includes a plasma treatment space containing layer (i) at a concentration of 0.03 to 30 W / cm². 2 The effective power density generates atmospheric pressure glow discharge plasma, preferably lasting less than 120 seconds. Preferably, the processing space is oxygen-free (e.g., the processing space contains an oxygen-free inert gas).

[0096] In step (b), the plasma treatment process preferably includes a treatment space containing layer (ii) at a plasma concentration of 0.1 to 30 W / cm². 2 The effective power density generates atmospheric pressure glow discharge plasma, preferably lasting less than 60 seconds. Preferably, the processing space in step (b) contains an oxygen-containing atmosphere (e.g., oxygen or air).

[0097] Therefore, preferably, step (a) of the method of the present invention is carried out in an oxygen-free atmosphere, and step (b) is carried out in an oxygen-containing atmosphere.

[0098] Atmospheric pressure glow discharge plasma typically utilizes precursor compounds (especially organosilicon compounds). The precursor compounds can be contained within the processing space and are preferably present at concentrations ranging from 0.3 to 9.0 J / cm². 2 The energy input level is carried out (in steps (a) and (b)).

[0099] In a preferred embodiment, the processing space in step (b) comprises an air atmosphere, and uses an intensity of 0.3 to 20.0 J / cm². 2 Energy input level.

[0100] In a preferred embodiment, step (a) and / or step (b) includes, for example, stabilizing the atmospheric pressure glow discharge plasma according to any method described in, for example, US6774569 and EP1383359.

[0101] In a preferred embodiment, step (b) includes exposing layer (ii) to atmospheric pressure glow discharge plasma, wherein the plasma is stabilized, for example, by an inductor-capacitor (LC) matching network as described in EP1917842. This embodiment provides a thin layer with very abundant functional groups of formula (1).

[0102] In another embodiment, layer (iii) (DL) can be applied to layer (ii) using plasma processing in a low-pressure plasma environment as described in US10,427,111.

[0103] In another embodiment, the plasma processing apparatus may include a transport device for transporting layer (i) (the support layer) or a combination of layers (i) and (ii) past the electrodes. Additionally, the transport device may include a tensioning mechanism for maintaining layer (i) or layer (i) and (ii) in close proximity to the electrodes.

[0104] In one embodiment, layer (ii) (BL) may be obtained from a precursor compound contained in the processing space. Precursor compounds that can be used to provide groups of formula (1) (as defined above) and optionally groups of formula (2) (as defined above) include TEOS (tetraethyl orthosilicate), HMDSO (hexamethyldisiloxane), TMOS (tetramethyl orthosilicate), TMCTS (1,3,5,7-tetramethylcyclotetrasiloxane), D4 OMCTS (octamethylcyclotetrasiloxane), D5 (decamethylcyclopentasiloxane), D6 (dodecylmethylcyclohexasiloxane), silane (SiH4), bis(triethoxysilyl)ethane (BTESE), TPOT (tetrapropyl orthotitanate), TEOT (titanium ethoxide), TTIP (tetraisopropoxide), ZTB (tetra-tert-butoxide zirconium), Zr(N(C2H5)2)4 or (Cp)Zr(N(CH3)2)3 or TMA (trimethylaluminum), and mixtures containing two or more of these. Other organosilicon or organometallic monomers that provide the properties described above for layer ii can also be used, such as HDMSN (hexamethyldisilazane), silane, and DVTMDSO (divinyltetramethyldisilazane).

[0105] In an alternative embodiment, step (b) of the method of the second aspect of the invention is formed by a precursor compound forming a layer (iii) (DL), for example, as described above for forming layer (ii) in step (a). Precursor compounds that can be used to provide groups of formula (1) (as defined above) and optional groups of formula (2) (as defined above) include TEOS (tetraethyl orthosilicate), HMDSO (hexamethyldisiloxane), TMOS (tetramethyl orthosilicate), TMCTS (1,3,5,7-tetramethylcyclotetrasiloxane), D4 OMCTS (octamethylcyclotetrasiloxane), D5 (decamethylcyclopentasiloxane), D6 (dodecylmethylcyclohexasiloxane), silane (SiH4), bis(triethoxysilyl)ethane (BTESE), TPOT (tetrapropyl orthotitanate), TEOT (titanium ethoxide), TTIP (tetraisopropoxide), ZTB (tetra-tert-butoxide zirconium), Zr(N(C2H5)2)4 or (Cp)Zr(N(CH3)2)3 or TMA (trimethylaluminum), and mixtures containing two or more of them.

[0106] The groups of formula (1) (as defined above) and optionally the groups of formula (2) (as defined above) can be derived from the precursor compound in the presence of O2 (e.g., in the form of air). The groups of formula (1) (as defined above) and optionally the groups of formula (2) (as defined above) are deposited on layer (i) to form BL, and deposited on layer (ii) to form DL. A uniform BL (layer ii) can be prepared using an atmospheric pressure glow discharge apparatus as described in EP1917842, with an average thickness preferably of 1 to 1,000 nm and an atomic percentage of M in M-(O-)x (groups of formula (1)) of 4 to 10 (e.g., 4.5 to 9).

[0107] Therefore, in one embodiment of the method of the second aspect of the invention, layers (ii) (BL) and (iii) (DL), each comprising a group of formula (1) (and optionally a group of formula (2)), are formed by plasma treatment of layers (i) and (ii), respectively. In another embodiment of the method of the second aspect of the invention, layers (ii) (BL) and (iii) (DL), each comprising a group of formula (1) (and optionally a group of formula (2)), are formed independently by deposition onto layers (i) and (ii), preferably using precursor compounds.

[0108] In another embodiment of the product of the present invention, the gas separation membrane of the first aspect of the present invention can be obtained by a method comprising the following steps: 1) at 0.3 to 9 J / cm 2 The energy input level, in the absence of oxygen, deposits the precursor onto the porous layer (i) to form layer (ii); and 2) at 0.3 to 20 J / cm2 The energy input level is used to plasma process layer (ii) in the presence of oxygen, thereby forming layer (iii) on top of layer (ii).

[0109] As described above, layer (i) preferably includes a trench layer (“GL”). The GL (when present) is preferably attached to the PSM.

[0110] GL is gas-permeable, although it typically has a low ability to distinguish between gases. When present, GL preferably comprises a polymer resin, particularly a polysiloxane.

[0111] Preferably, the polysiloxane present in or as GL is a poly(dimethyl)siloxane, such as a polymer containing -Si-(CH3)2-O- repeating units.

[0112] The average thickness of GL is preferably 50 to 2400 nm, more preferably 150 to 800 nm, and particularly 200 to 650 nm.

[0113] Preferably, the GL contains groups capable of bonding with a metal, for example through covalent bonds, ionic bonds, and / or through hydrogen bonds, preferably through covalent bonds. The properties of such groups depend to some extent on the chemical composition of the GL and the properties of the metal, but typically these groups are selected from epoxy groups, oxetyl groups, carboxylic acid groups, amino groups, hydroxyl groups, vinyl groups, hydrogen groups, and thiol groups. More preferably, the GL contains a polymer having carboxylic acid groups, epoxy groups or oxetyl groups, vinyl groups, hydrogen groups, or combinations of two or more of these groups. This polymer can be formed on a support by a process involving curing a radiation-curable or thermosetting composition, particularly a curable (e.g., radiation-curable) composition containing a polymerizable dialkylsiloxane. The latter option can be used to provide a preferred GL containing a dialkylsiloxane group.

[0114] Polymerizable dialkylsiloxanes are preferably monomers containing dialkylsiloxane groups or polymerizable oligomers or polymers containing dialkylsiloxane groups. For example, GL can be prepared from a radiation-curable composition comprising a partially crosslinked radiation-curable polymer containing dialkylsiloxane groups, as described in more detail below. Typical dialkylsiloxane groups have the formula -{O-Si(CH3)2}n-, where n is at least 1, for example, from 1 to 100. Poly(dialkylsiloxane) compounds having terminal vinyl groups are also available, and these compounds can be incorporated into GL via a curing process.

[0115] In one embodiment, GL does not contain the group of formula Si-C6H5.

[0116] Irradiation of the radiation-curable composition (sometimes referred to as "curing" in this specification) can be performed using any source that provides the radiation wavelength and intensity required to polymerize the radiation-curable composition and thereby form a GL on the PSM, thus forming an optional GL. For example, electron beams, ultraviolet (UV), visible and / or infrared radiation can be used to irradiate (cur) the radiation-curable composition, wherein a suitable radiation is selected to match the components of the composition.

[0117] Optional GL is preferably obtained by curing a curable composition, said curable composition comprising:

[0118] (1) 0.5 to 25% by weight of a radiation-curable component, wherein at least one comprises a dialkylsiloxane group;

[0119] (2) 0 to 5% by weight of a photoinitiator; and

[0120] (3) 70 to 99.5% by weight of inert solvent.

[0121] Preferably, the molar ratio of metal to silicon in the curable composition used to prepare GL is at least 0.0005, more preferably 0.001 to 0.1, and particularly 0.003 to 0.03.

[0122] The radiation-curable component of component (1) typically contains at least one radiation-curable group. Radiation-curable groups include olefinically unsaturated groups (e.g., (meth)acrylic acid groups (e.g., CH2=CR)). 1 C(O)- groups), especially (meth)acrylate groups (e.g., CH2=CR). 1 C(O)O- group), (meth)acrylamide group (e.g., CH2=CR) 1 C(O)NR 1 -group), wherein each R 1 Independently H or CH3), especially oxetane or epoxy group (e.g. glycidyl and epoxycyclohexyl).

[0123] The amount of radiation-curable component (i.e., component (1)) present in the curable composition for preparing GL and / or optional protective layer is preferably 1 to 20% by weight, more preferably 2 to 15% by weight. In a preferred embodiment, component (1) of the curable composition for preparing GL and / or protective layer comprises a partially crosslinked radiation-curable polymer containing dialkylsiloxane groups.

[0124] The function of the inert solvent (3) is to provide a composition with a viscosity suitable for a specific method of applying the curable composition to the support. For high-speed application methods, low-viscosity inert solvents are typically chosen. Examples of suitable inert solvents have been mentioned above regarding the preparation of polymer sheets.

[0125] The amount of the inert solvent (3) (i.e. component (3)) present in the curable composition used to prepare the GL and / or protective layer is preferably 70 to 99.5% by weight, more preferably 80 to 99% by weight, and particularly 90 to 98% by weight.

[0126] Inert solvents are non-radiation curable.

[0127] The composition may contain other components, such as surfactants, surface tension modifiers, thickeners, biocides and / or other components that can copolymerize with other ingredients.

[0128] Layer (iv) (if present) helps improve the crack resistance of the gas separation membrane. Layer (iv) can be provided by, for example, the method described in GB2104461.5. Preferably, layer (iv) (if present) comprises at least two different fluorinated polymers, such as a silicone-free perfluorinated polymer and a silicone-containing fluoropolymer.

[0129] Examples of suitable silicon-free perfluoropolymers include poly[4,5-difluoro-2,2-bis(trifluoromethyl)-1,3-dioxacyclopentene-co-tetrafluoroethylene] having 60 to 90 mol% dioxacyclopentene, preferably 87 mol% dioxacyclopentene. AF 2400 is obtained from Chemous; poly[4,5-difluoro-2,2-bis(trifluoromethyl)-1,3-dioxacyclopentene-co-tetrafluoroethylene] having 50 to 80 mol% dioxacyclopentene, preferably 65 mol% dioxacyclopentene (as... AF 1600 (obtained from Chemous); from A series of perfluorinated polymers (from AGC Chemicals Company); and amorphous poly(tetrafluoroethylene-2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxacyclopentene), wherein the proportion of ether functional groups is preferably 30 to 90 mol%, preferably 40, 60 or 80 mol% (e.g., can be used as...). AD 60 or AD 40H (obtained from Solvay).

[0130] Silicon-containing fluoropolymers include compounds of formula (3), wherein the values ​​of m and n are each independently at least 1, and the average molecular weight (NAMW) of the compounds of formula (3) is 500 to 10,000 Daltons, particularly 550 to 9,000 Daltons, and even more particularly 560 to 8,000 Daltons:

[0131] (CH3CH2O)3Si-(CH2)3-NH-C(O)-CF2O-[-(CF2CF2O)m -(CF2O) n -]-CF2-C(O)-NH-(CH2

[0132] )3-Si(OCH2CH3)3

[0133] Equation (3)

[0134] The average thickness of layer (iv) (if present) is preferably at least 50 nm. Preferably, the average thickness of layer (iv) is less than 500 nm. In a preferred embodiment, the average thickness of layer (iv) is 50 to 500 nm, more preferably 60 to 400 nm, and even more preferably 70 to 250 nm, because this allows layer (iv) in the GSM not to interfere with the DL's ability to distinguish between polar and nonpolar gases.

[0135] Typically, layer (iv) is located on layer (iii).

[0136] An optional protective layer (v) (“PL”) is the outermost layer, for example, located on layer (iv) (if layer (iv) exists), or on layer (iii) (if layer (iv) does not exist). PL may be made of the components described above with respect to GL, and may have the same composition as GL or a different composition than GL. The function of PL is to protect the underlying layer, such as layer (iii) or (iv), as appropriate.

[0137] Preferably, the average thickness of layer (v)(PL) is 100 to 3,000 nm, more preferably 1,000 to 2,000 nm.

[0138] The gas separation membrane of the present invention can be packaged and commercially supplied to companies that assemble gas separation modules, for example for their own use or for continued sale.

[0139] According to a third aspect of the present invention, a gas separation module is provided, which includes one or more gas separation membranes of the first aspect of the present invention.

[0140] The gas separation module of the present invention preferably further includes a feed carrier and a permeate carrier optionally wound onto a perforated tube.

[0141] Preferred gas separation modules include spiral modules, hollow fiber modules, pleated modules, tubular modules, and plate-and-frame modules.

[0142] According to a fourth aspect of the invention, a gas separation membrane of the first aspect of the invention or a gas separation module of the third aspect of the invention is provided for use in separating gases and / or for purifying feed gases.

[0143] The gas separation membrane and module of the present invention are particularly suitable for separating a feed gas containing a target gas into a gas stream rich in the target gas and a gas stream deficient in the target gas. For example, a feed gas containing both polar and nonpolar gases can be separated into a gas stream rich in polar gases and a gas stream deficient in polar gases. In many cases, the membrane is more effective against polar gases (e.g., CO2, H2S, NH3, SO2) than against nonpolar gases (e.g., alkanes, H2, and N2). x and nitrogen oxides, especially NO x It has high permeability. Therefore, the preferred polar gas is CO2, H2S, NH3, SO2. x Nitrogen oxides or combinations thereof. Nonpolar gases are preferably N2, H2, alkanes or combinations thereof.

[0144] Preferably, the polar and non-polar gases are in a gaseous state at 25°C.

[0145] The target gas can be, for example, a gas that is valuable to the user of the module or component and that the user wishes to collect. Alternatively, the target gas can be an undesirable gas, such as a pollutant or "greenhouse gas," that the user wishes to separate from the gas stream in order to meet product specifications or protect the environment.

[0146] The modules and membranes of this invention are particularly suitable for purifying natural gas (a mixture primarily containing methane) by removing polar gases (CO2, H2S); for purifying syngas; and for removing CO2 from hydrogen and flue gas. Flue gas is typically generated from fireplaces, ovens, furnaces, boilers, internal combustion engines, and power plants. The composition of flue gas depends on the material being burned, but it typically contains primarily nitrogen from the air (usually more than two-thirds) and carbon dioxide (CO2) from combustion. Flue gas also contains low percentages of pollutants such as particulate matter, carbon monoxide, nitrogen oxides, and sulfur oxides. Recently, the separation and capture of CO2 has attracted attention related to environmental issues (global warming).

[0147] The modules and membranes of the present invention are particularly suitable for the following separations: separating a feed gas containing CO2 and N2 into a gas stream richer in CO2 than the feed gas and a gas stream less CO2 than the feed gas; separating a feed gas containing CO2 and CH4 into a gas stream richer in CO2 than the feed gas and a gas stream less CO2 than the feed gas; separating a feed gas containing CO2 and H2 into a gas stream richer in CO2 than the feed gas and a gas stream less CO2 than the feed gas; separating a feed gas containing H2S and CH4 into a gas stream richer in H2S than the feed gas and a gas stream less H2S than the feed gas; and separating a feed gas containing H2S and H2 into a gas stream richer in H2S than the feed gas and a gas stream less H2S than the feed gas.

[0148] The modules and membranes of the present invention are particularly suitable for separating “dirty” feed gases containing polar gases, non-polar gases, and hydrocarbons containing at least two (e.g., 2 to 7) carbon atoms into permeate gases and permeate gases, one of which is rich in polar gases and the other is poor in polar gases.

[0149] The invention will now be illustrated by the following non-limiting examples, wherein all parts and percentages are by weight unless otherwise stated. Example

[0150] In these embodiments, the performance of the gas separation membrane was measured using a multilayer structure comprising the gas separation membrane under test (05TH100S sheet and 42369 sheet) having the general structure shown in Table 1.

[0151] 05TH100S sheet material is from Hirose Paper Mill (wet-laid polyester nonwoven fabric / average thickness 100μm / average weight 100g / m²) 2 The average density is 0.93 g / cm³. 3 42369 sheet is a macroporous sheet from Guilford (a fabric made of polyethylene terephthalate and epoxy resin with an average thickness of 0.3 mm, 60 wpi (number of rows per 2.54 cm) and 59 cpi (number of rows per 2.54 cm)). Together with 05TH100S sheet, 42369 sheet serves as an imprint sheet for testing gas separation membranes under high-pressure feed and temperature conditions.

[0152] Table 1

[0153] 05TH100S sheet 42369 sheet

[0154] In the embodiments, the composition of the feed gas used is shown in Table 2 below:

[0155] Table 2

[0156]

[0157] The performance properties of the gas separation membrane of the present invention were measured using the multilayer structure shown in Table 1 and the following techniques.

[0158] (A) Penetration rate:

[0159] The feed gas, having the composition described in Table 2 above, was passed through the multilayer structure shown in Table 1 at 40°C and a gas feed pressure of 6000 kPa. CO2 and n-C4H were measured using a gas permeation cell with a measuring diameter of 2.0 cm. 10The flux of CH4 and the complex through simplified gas separation.

[0160] After continuous use on the gas separation complex for 5 minutes, CO2 and n-C4H were determined using the following formula. 10 and the penetration rate of CH4 (Q) i ):

[0161] Q i =(θ Perm ·X Perm,i ) / (A·(P Feed ·X Feed,i -P Perm ·X Perm,i ))

[0162] in:

[0163] Q i = Permeability of the relevant gas (i.e., i is CO2 or n-C4H) 10 or CH4)(m 3 (STP) / m 2 (kPa·s);

[0164] θ< Perm = Permeation velocity (m) 3 (STP) / s);

[0165] X Perm,i = Volume fraction of the relevant gas in the permeating gas;

[0166] A = membrane area (m²) 2 );

[0167] P Feed = Feed gas pressure (kPa);

[0168] X Feed,i = Volume fraction of relevant gases in the feed gas;

[0169] P Perm = Osmotic gas pressure (kPa); and

[0170] STP stands for Standard Temperature and Pressure, which is defined here as 25.0°C and 1 atmosphere (101.325 kPa).

[0171] (Q i ) can be achieved with 1 GPU = 1 × 10 -6 cm 3 (STP) / (s·cm 2 It is determined by (·cmHg).

[0172] CO2 penetration rates above 25 GPUs were assessed as acceptable, while those below or equal to 25 GPUs were considered unacceptable.

[0173] (B) Selectivity

[0174] The selectivity of each gas separation complex tested for the gas mixtures described in Table 2 (CO2 / C4H) 10 and CO2 / CH4; αCO2 / C4H 10 (and αCO2 / CH4) is composed of QCO2 and Qn-C4H 10 Calculate QCO2 and Qn-C4H as described above. 10 Based on the following equation:

[0175] αCO2 / n-C4H 10 =QCO2 / Qn-C4H 10 ;

[0176] αCO2 / CH4=QCO2 / QCH4

[0177] Among them, QCO2, QCH4 and Qn-C4H 10 The determination is performed using the method described in step (A) above.

[0178] αCO2 / n-C4H above 100 10 Values ​​below 100 for αCO2 / n-C4H are considered acceptable. 10 The value is considered unacceptable.

[0179] An αCO2 / CH4 value above 26 is considered acceptable, while an αCO2 / CH4 value below 26 is considered unacceptable.

[0180] (C) Imprint performance test

[0181] Imprint performance was measured as follows:

[0182] The gas separation membrane is placed on top of other layers as shown in Table 1 above, thereby providing a stack of sheets. Each sheet is circular and has a diameter of 48 mm.

[0183] A stack of sheets was placed in a chamber and a gas mixture containing O2 and N2 was applied to the membrane side at 60°C and a pressure of 100 bar for 30 minutes. The pressure was then reduced to atmospheric pressure and repressurized under the same conditions for a total of 5 cycles. The gas separation membrane to be tested was then removed from this set of sheets, thus providing the imprinted membrane. The same gas separation and evaluation were then performed on the imprinted membrane by repeating (5 times) the above flux (A) and selectivity (B) tests to measure the imprinting performance, i.e., the extent to which the sheet imprints its texture onto the gas separation membrane.

[0184] (D) Scratch (shear stress) test

[0185] The following measures were taken to determine the extent to which the performance of the gas separation membrane was affected by scratching:

[0186] The gas separation membrane under test was placed in a Heidon 14DR apparatus for surface property testing. The measuring head (8 mm in diameter, 10 mm in width) was covered with a large-pore 42369 sheet from Guilford (a fabric made of polyethylene terephthalate and epoxy resin, with an average thickness of 0.3 mm, 60 wpi (number of rows per 2.54 cm) / 59 cpi (number of rows per 2.54 cm)), and the measuring head was placed on a 300 g membrane. The measuring head, with pads and weights, was moved 80 times across the membrane surface to simulate scratch and shear stresses on the membrane under test.

[0187] The scratch performance, i.e. the degree to which the membrane performance is affected by scratching, is then evaluated by performing flux (A) and selectivity (B) tests before and after the aforementioned scratching and comparing the results.

[0188] Preparation of gas separation membrane

[0189] The following materials were used to prepare the gas separation membrane:

[0190] PAN1 is a porous sheet with an average thickness of 170-180 μm, containing a PET nonwoven support (140-150 μm thick) with a porous polyacrylonitrile layer. PAN1 is sourced from Microdyn-Nadir GmbH, Germany, and is marketed under the name UA100T, containing 3.5 mg / m³. 2 Na + (Sodium ions).

[0191] PAN2 is a porous sheet with an average thickness of 180-190 μm, containing a 140-150 μm thick PET nonwoven support with a porous polyacrylonitrile layer. PAN2 is sourced from GMT Membrantechnik GmbH in Germany and is marketed as L14.

[0192] X-22-162C is a double-ended reactive organosilicon with a carboxylic acid reactive group and a viscosity of 220 mm. 2 / s and the equivalent of the reactive group is 2,300 g / mol, which comes from Shin-Etsu Chemical Co., Ltd. (MWT 4,600) (l is an integer).

[0193]

[0194] DBU is 1,8-diazabicyclo[5.4.0]undec-7-ene from Sigma Aldrich.

[0195] UV-9300 is from Momentive Performance Materials Holdings' SilForce. TM UV-9300 has an epoxy equivalent of 950 g / mol ethylene oxide (MWT 9,000, determined by viscosity) (m and n are integers).

[0196]

[0197] HYFLON™ AD 60 is an amorphous poly(tetrafluoroethylene-co-2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxane), preferably with an ether functional group ratio of 30 to 90 mol%, more preferably 60 mol%, for example, that can be obtained from Solvay (a silicon-free perfluorinated fluoropolymer).

[0198] D4484 is 1,1,1,2,2,3,4,5,5,5-decafluoro-3-methoxy-4-(trifluoromethyl)pentane (solvent) from Tokyo ChemicaI Industry.

[0199] I0591 is 4-isopropyl-4'-methyldiphenyliodotetra(pentafluorophenyl)borate (C) from Tokyo Chemical Industries NV (Belgium). 40 H 18 BF 20 I).

[0200]

[0201] Ti(OiPr)4 is titanium isopropoxide (IV) (MWT 284) from Dorf Ketal Chemicals.

[0202] n-Heptane is n-heptane derived from Brenntag Nederl and BV.

[0203] MEK is 2-butanone derived from Brenntag Nederl and BV.

[0204] QM1 is VQM-146, a vinyl-functionalized QM resin dispersion from Gelest Inc. in a bivinyl-terminated vinyl-functionalized polydimethylsiloxane, having the following formula:

[0205]

[0206] MIBOH is 2-methyl-3-butyn-2-ol from Sigma-Aldrich.

[0207] HMS-301 is a poly(methylhydrosiloxane-co-dimethylsiloxane) from Gelest Inc.

[0208] PT is SIP6831.2, a platinum(0)-1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex in xylene from Gelest Inc.

[0209] Si-1 is a fluoropolymer containing silicon and of formula (3) as shown above, with an average molecular weight of 1,750 to 1,950 Daltons (from Solvay).

[0210] TTIP is tetraisopropoxide titanium (97%) supplied by Merck, which is used as a precursor for the buffer layer (ii).

[0211] HMDSO is a hexamethyldisiloxane (98%) supplied by Merck, which is used as a precursor for the buffer layer (ii).

[0212] TMCTS is a 1,3,5,7-tetramethylcyclotetrasiloxane (>98.5%) supplied by Merck, which is used as a precursor for the buffer layer (ii).

[0213] 05TH100S is a sheet material from Hirose Paper Mill (wet-laid polyester nonwoven fabric / average thickness 100μm / average weight 100g / m²). 2 The average density is 0.93 g / cm³. 3 )

[0214] 42369 sheet is a sheet from Guilford (a fabric made of polyethylene terephthalate and epoxy resin / average thickness 0.3mm / 60wpi (number of rows per 2.54cm) / 59cpi (number of rows per 2.54cm)).

[0215] Membrane preparation

[0216] Stage a) Preparation of partially cured polymer ("PCP polymer")

[0217] Components UV-9300, X-22-162C, and DBU were dissolved in n-heptane in the amounts shown in Table 3 and maintained at 91 °C for 168 hours. The resulting polymer (PCP polymer) had a Si content (meq / g polymer) of 12.2, and the viscosity of the resulting PCP polymer solution at 25.0 °C was 125 mPas.

[0218] Table 3 – Components used to prepare PCP polymers

[0219] UV-9300 (wt%) 46.395 X-22-162C (wt%) 13.596 DBU (by weight%) 0.009 n-Heptane (wt%) 40.000

[0220] Stage b) Preparation of radiation-curable composition C

[0221] The PCP polymer solution from step a) was cooled to 20°C and diluted with n-heptane to obtain the PCP polymer concentrations shown in Table 4 below. The solution was then filtered through filter paper with a pore size of 2.7 μm. A photoinitiator (I0591) and a metal complex (Ti(OiPr)4) were then added in the amounts (wt%) shown in Table 4 to obtain curable composition C. The amount of Ti(OiPr)4 present in curable composition C corresponds to 55.4 μmol of Ti(OiPr)4 / g PCP polymer. Furthermore, the molar ratio of metal to silicon in curable composition C is 0.0065.

[0222] Table 4 – Components of Curable Composition C

[0223] PCP polymer 10.000 I0591 0.105 <![CDATA[Ti(OiPr)4]]> 0.226 DBU 0.001 MEK 2.008 n-Heptane 87.660

[0224] Curable composition C is used to prepare the trench layer (“GL”) and protective layer (“PL”) of a gas separation membrane, as described in more detail below.

[0225] Stage c) Preparation of resin precursor groups for comparative examples Co-Ex2 and Co-Ex3 (which lack the buffer layer of the present invention) Compounds

[0226] Add the components mentioned in Table 5 below at the specified concentrations and stir at room temperature for 5 minutes to prepare a curable polysiloxane polymer solution. Filter the solution through a 0.5 μm polypropylene filter before use.

[0227] Table 5 – Composition of the resin precursor composition

[0228] QM1 2.294 HMS-301 0.206 PT 0.0075 MIBOH 0.0075 n-Heptane 97.485

[0229] Stage d) Preparation of the composition for forming layer (iv) (FPL) ("Composition D1")

[0230] Apply the amounts shown in Table 6 below to Hyflon TM AD60 was mixed with a solvent (D4484 from Tokyo ChemicaI Industry, 1,1,1,2,2,3,4,5,5,5-decafluoro-3-methoxy-4-(trifluoromethyl)pentane). The mixture was stirred in a sealed flask at 25°C for 30 hours. S-1 was then added and the mixture was stirred at 20°C for 1 hour. The solution was then filtered through 2.7 μm filter paper to provide composition D1.

[0231] Table 6 – Preparation of Composition D1

[0232]

[0233] Composition D1 is used to prepare the layer (iv) (“FPL”) of a membrane, as described in more detail below.

[0234] Step i. Prepare a support layer (i) comprising a porous sheet ("PSM") and a trench layer (GL) (PSM-GL)

[0235] Curable composition C (containing polyacrylonitrile (PAN)) was applied to PAN1 or PAN2 sheets via meniscus dip coating at a speed of 10 m / min, followed by irradiation of the coated porous sheets using a Light Hammer LH10 from Fusion UV Systems equipped with a D-bulb at an intensity of 16.8 kW / m (70%). The resulting support layer comprised the porous sheet and a 600 nm thick polysiloxane (PDMS) trench layer. The trench layer contained metal complexes and dialkylsiloxane groups. The thickness of the trench layer was determined by cutting through the support layer and measuring the thickness from the surface of the porous sheet outward using SEM.

[0236] Comparative supports comprising porous sheet material (PSM), grooved layer (GL), and resin precursor layer (RPL) on GL. Layers (Comparison Examples 2 and 3 (PSM+GL+RPL))

[0237] The resin precursor composition described in Table 5 above was applied to the GL (porous sheet + GL) of the product from step (i) at a speed of 10 m / min using a pre-formed grooved mold (as described in Table 7 below). The resulting product was then heated to 60°C for 10 minutes. The resulting product sequentially comprised a porous sheet (PSM) + a grooved layer (GL) + a resin precursor layer (RPL). This is a comparative layer because RPL was used instead of the layer (ii) of the present invention. The thickness of the resin precursor layer was determined to be 150 nm by cutting through the support layer (i.e., the PSM+GL) + RPL composite and measuring the thickness from the surface of the support layer outward by SEM, as shown in Table 7 below.

[0238] Step iii. Forming a buffer layer (BL)

[0239] Samples from the support layer (i) of step i were each independently exposed to atmospheric pressure glow discharge (APG) plasma using different precursors (HMDSO, TMCTS, and TTIP, as shown in Table 7 below). The equipment used for exposure was as described in EP1917842. Precursor mass flow rates of 1.0 g / hr for HMDSO, 0.5 g / hr for TMCTS, and 1.0 g / hr for TTIP were provided via a controlled evaporation unit. The precursor vapors were diluted in an argon processing carrier gas. The process gas flow rate was 20 dm³. 3 (STP) / min. In all cases, the applied plasma power density was 0.4 W / cm². 2The thickness of the resulting buffer layer depended on the precursors and conditions used (processing time of 5 to 15 seconds), and the thickness of the buffer layer for each gas separation membrane was confirmed by cutting through the PMS(+GL)+BL composite and measuring the thickness using scanning electron microscopy. The energy input level for Examples 1 to 4 was 2.0 J / cm². 2 Examples 5 and 6 show a concentration of 4.0 J / cm³. 2 Example 7 shows a concentration of 1.5 J / cm. 2 The energy input level in Example 8 is 1.6 J / cm². 2 The energy input level of Example 9 is 4.0 J / cm². 2 Furthermore, the energy input level of Example 10 is 6 J / cm². 2 .

[0240] Step iv. Forming the porous support + RPL for the comparative example (from step ii) and the embodiment (from step ii). (iii) The porous support + BL) and the discrimination layer (DL)

[0241] The products of steps ii and iii were respectively exposed to an additional atmospheric pressure glow discharge (APG) plasma in the presence of oxygen (O2) to form a discrimination layer in the examples and comparative examples. This can be contrasted with the preparation of BL, in which the APG plasma treatment was performed under oxygen-free (O2) conditions.

[0242] For Examples 1 to 10 and Comparative Examples 1 to 3, the atmospheric plasma apparatus for forming DL is as shown in Figure 5 of EP1917842, wherein an oxygen flow rate of 0.5 dm is set. 3 (STP) / min and argon flow rate of 20 dm 3 The carrier gas condition was (STP) / min, followed by plasma treatment as oxygen atom permeation, wherein the input power in Example 1 was 1.75 J / cm³. 2 The input power for all other embodiments is 0.9 J / cm². 2 .

[0243] The presence of the groups of formula (1) in DL and BL in the various embodiments and comparative examples as described above, and the atomic percentage of M of formula (1) on the surface, were determined, and the results are listed in Table 7 below.

[0244] Step iv. Forming a fluoropolymer layer ("FPL") in Examples 4 and 6 and Comparative Example 3.

[0245] In Examples 4 and 6 and Comparative Example 3, the membrane was dip-coated onto the meniscus of composition D1 (as described above) at a speed of 10 m / min, and the resulting gas separation membrane was then dried to provide an FPL. The thickness of the resulting layer (iv) (FPL) was determined by cutting through the membrane and measuring the thickness from the top layer using SEM.

[0246] Step v. Forming the protective layer ("PL") of Examples 2 to 10 and Comparative Examples 1 to 3

[0247] In Examples 2 to 10 and Comparative Examples 1 to 3, PL was applied as follows:

[0248] In Examples 2 to 10 and Comparative Examples 1 to 3, the curable composition C having the above formulation was applied to all the described films by meniscus dip coating at a speed of 10 m / min to obtain PL. The coated films were then cured by irradiation with a Light Hammer LH10 from Fusion UV Systems equipped with a D lamp at an intensity of 24 kW / m. The average thickness of each protective layer (v) was measured to be 2400 nm by SEM.

[0249] Table 7 shows the composition of each gas separation membrane in the examples and comparative examples in more detail.

[0250] Table 8 shows the selectivity and permeability of the gas separation membranes produced in the examples and comparative examples before and after imprinting.

[0251] Table 9 shows the selectivity and permeability of the gas separation membranes produced in the examples and comparative examples before and after the scratch test.

[0252] As can be seen from Tables 8 and 9, the embossing and scratching of the gas separation membrane of the present invention significantly reduced its selectivity and permeability compared to the comparative examples.

[0253] Table 7

[0254]

[0255]

[0256]

[0257] Note: Comparative Examples 1 to 3 do not contain the layer (ii) of the present invention; in contrast, Comparative Examples 2 and 3 contain RPL.

[0258] Table 8

[0259]

[0260] NG = bad; OK = good

[0261] Table 9

[0262]

[0263] NG = bad; OK = good

Claims

1. A gas separation membrane comprising the following layers: (i) Support layer; (ii) Using a buffer layer formed by plasma treatment of a precursor; (iii) Discrimination layer; (iv) An optional fluoropolymer layer; and (v) Optional protective layer; in, (a) The buffer layer (ii) and the discrimination layer (iii) each independently contain groups of formula (1): M-(O-) x Equation (1) in: Each M is independently silicon or titanium; O represents an oxygen atom; and Each x value is independently at least 4; (b) The buffer layer (ii) comprises a surface of M containing 4 to 10 atomic percent of a group of formula (1), wherein M is as defined above; (c) The distinguishing layer (iii) comprises a surface of M containing more than 10 atomic percent of a group of formula (1), wherein M is as defined above; and (d) The buffer layer (ii) is located between the support layer (i) and the discrimination layer (iii).

2. The gas separation membrane as described in claim 1, wherein, The plasma treatment is performed using the following precursors: tetraethyl orthosilicate, hexamethyldisiloxane, tetramethyl orthosilicate, 1,3,5,7-tetramethylcyclotetrasiloxane, octamethylcyclotetrasiloxane, decamethylcyclopentasiloxane, dodecylcyclohexasiloxane, SiH4, bis(triethoxysilyl)ethane, tetrapropyl orthotitanate, titanium ethoxide, or titanium tetraisopropoxide.

3. The gas separation membrane as described in claim 1, wherein, The discrimination layer is formed by plasma treatment.

4. The gas separation membrane as described in claim 3, wherein, The buffer layer (ii) comprises a surface of M containing 4.5 to 9 atomic percent of the groups of formula (1).

5. The gas separation membrane as described in claim 3, wherein, The oxygen-carbon ratio (O / C) of the buffer layer (ii) is greater than 0.7 to 1.

7.

6. The gas separation membrane as described in claim 1, wherein, The oxygen-silicon ratio (O / total Si) of the discrimination layer (iii) is 1.8 to 100.

7. The gas separation membrane as described in claim 1, wherein, The atomic percentage of M in the buffer layer (ii) is substantially constant over the entire thickness of the buffer layer (ii), and the atomic percentage of M in the discrimination layer (iii) decreases as the distance from the buffer layer (ii) decreases.

8. A method for forming the gas separation membrane of claim 1, comprising the following steps: (a) The buffer layer (ii) is applied to the support layer (i) by plasma treatment in an oxygen-free atmosphere; and (b) The discrimination layer (iii) is applied to the buffer layer (ii) by plasma treatment in an oxygen-containing atmosphere.

9. A gas separation module comprising the gas separation membrane of claim 1.

Citation Information

Patent Citations

  • Method and arrangement for treating a substrate with an atmospheric pressure glow plasma (APG)

    EP1383359A2

  • Method and arrangement for generating and controlling a discharge plasma

    EP1917842A1

  • Gas separation membranes

    GB202104461D0

  • Gas separation membrane, method of producing gas separation membrane, gas separation membrane module, and gas separator

    US10427111B2

  • Apparatus for producing and sustaining a glow discharge plasma under atmospheric conditions

    US6774569B2